2015
DOI: 10.3989/arbor.2015.771n1006
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognised Rights, Nonexistent Laws. The Invisibility of Foreign Teenage Mothers: A Challenge for Social Work in Spain

Abstract: This paper addresses the reality of foreign teenage motherhood in Spain. Its importance lies not in its quantitative dimension but the implications for a growing number of girls who face motherhood at an early age. Thus, after analysing the determinants of such pregnancies, the characteristics of the phenomenon in Spain are discussed highlighting the apparent inconsistencies between this reality and the regulatory framework. In analysing the protection policies we restrict ourselves to Andalusia as a territori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…The adolescent enters motherhood with the consequent family and social stigmatization, implicit feelings of guilt, shame, low self-esteem and a certain impossibility of feelings, emotions, decisions and positive evaluations (Salinas, 2019). This usually happens because early motherhood is often determined by limited family support (Álvarez et al, 2015;Amar et al, 2013;Pesce et al, 2005), the absence or violent intervention of the father in the home; aspects that hinder the formation of adolescent self-regulation (Artuch et al, 2017), poverty, marginalization, low educational level, family violence and sexual ignorance (Arias & Rivera, 2021;Catacora, 2011). In contrast, some authors have identified some protective factors for early motherhood, such as good interpersonal communication, high self-esteem, having an elaborated and internalized life project, having a well-established internal locus of control, an elaborated sense of life, assistance to school and a high level of resilience (Páramo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The adolescent enters motherhood with the consequent family and social stigmatization, implicit feelings of guilt, shame, low self-esteem and a certain impossibility of feelings, emotions, decisions and positive evaluations (Salinas, 2019). This usually happens because early motherhood is often determined by limited family support (Álvarez et al, 2015;Amar et al, 2013;Pesce et al, 2005), the absence or violent intervention of the father in the home; aspects that hinder the formation of adolescent self-regulation (Artuch et al, 2017), poverty, marginalization, low educational level, family violence and sexual ignorance (Arias & Rivera, 2021;Catacora, 2011). In contrast, some authors have identified some protective factors for early motherhood, such as good interpersonal communication, high self-esteem, having an elaborated and internalized life project, having a well-established internal locus of control, an elaborated sense of life, assistance to school and a high level of resilience (Páramo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(p. 81) Sumado a ello, a partir de 1990 surgen nuevas problemáticas que generan nuevos perfiles de atención en los sistemas de protección a la infancia y la adolescencia en España. Entre otros, la llegada de niños/as y adolescentes extranjeros no acompañados, menores de edad denunciados por su núcleo convivencial, en especial adolescentes con problemas de conducta y diagnósticos psicológicos y psiquiátricos que visibilizan problemas de salud mental (González, 2018), o maternidades adolescentes, especialmente, en chicas de origen extranjero (Álvarez-Pérez, Vázquez Aguado, & Fernández-Borrero, 2015).…”
Section: Evolución De Las Tipologías De Centros De Atención a La Infa...unclassified